Micro- and mesoporous carbide-derived carbon prepared by a sacrificial template method in high performance lithium sulfur battery cathodes - Oschatz, M.; Lee, J. T.; Kim, H.; Nickel, W.; Borchardt, L.; Cho, W. I.; Ziegler, C.; Kaskel, S.; Yushin, G. (Royal Society of Chemistry, 2014)
Polymer-based carbide-derived carbons (CDCs) with combined micro-and mesopores are prepared by an advantageous sacrificial templating approach using poly(methylmethacrylate) (PMMA) spheres as the pore forming material. Resulting CDCs reveal uniform pore size and pore shape with a specific surface area of 2434 m(2) g(-1) and a total pore volume as high as 2.64 cm(3) g(-1). The bimodal CDC material is a highly attractive host structure for the active material in lithium-sulfur (Li-S) battery cathodes. It facilitates the utilization of high molarity electrolytes and therefore the cells exhibit good rate performance and stability. The cathodes in the 5 M lithium bis(trifluoromethanesulfonyl) imide (LiTFSI) electrolyte show the highest discharge capacities (up to 1404 mA h g(s)(-1)) and capacity retention (72% after 50 cycles at C/5). The unique network structure of the carbon host enables uniform distribution of sulfur through the conductive media and at the same time it facilitates rapid access for the electrolyte to the active material.